Development of an aptitude test that measures language and visual-spatial abilities to identify potential academic vulnerability of students in anatomy - Humphries, Petro (Stellenbosch : Stellenbosch University, 2017)
Thesis (MPhil)-- Stellenbosch University, 2017.